Marriage Agreement Against Bankruptcy of Individuals Bound in Marriage - Marpaung, Michael Arthur Schumihar (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Prenuptial agreements are becoming increasingly important in the context of modern marriage law, especially in regulating rights and obligations before the marriage bond is formed. However, the situation becomes complex when one of the spouses faces individual bankruptcy after the marriage. This article discusses the legal impact of prenuptial agreements on the bankruptcy process of individuals who are bound by marriage. Through a legal analysis and case study approach, the author explores how prenuptial agreements can affect the rights and obligations of spouses in individual bankruptcy cases. In this context, consideration and justice are important to consider. In conclusion, if there is a marriage agreement in bankruptcy, the assets of each husband and wife are not included in the joint assets so that they can be used to pay off the personal debts of the husband or wife who is declared bankrupt.